IoT-enabled water quality sensor: Detecting concentration of saccharomyces boulardii bacteria to enhance water safety - Muhammad Aqil Hafizzan, Nordin; Mohd Faizal, Jamlos; Bakhit, Abdelmoneim Ahmed (Springer Singapore, 2024)
Water quality monitoring and detecting microorganisms are crucial for ensuring safe water resources. This study investigated the effectiveness of Internet of Things (IoT)-based sensors in measuring water parameters and detecting microorganisms, using Saccharomyces boulardii as a model microorganism. The study employed IoT-based sensors to measure key water parameters, including pH, dissolved oxygen (DO), electrical conductivity (EC), total dissolved solids (TDS), and temperature. The objectives were to assess the sensitivity and accuracy of the IoT sensor system in detecting the presence of microorganisms and to understand the impact of different concentrations of Saccharomyces boulardii on water parameters. The methodology involved inoculating the water with Saccharomyces boulardii and continuously monitoring the water parameters using IoT-based sensors. A significant increase in DO levels from 4 to 8 ppm after an hour of bacterial inoculation indicated that the DO sensor had successfully detected the presence of bacteria. However, after five hours, the DO level returned to normal, attributed to the yeast’s acclimation process. Moreover, the study examined the effect of varying Saccharomyces boulardii concentrations (50 and 100%) on DO readings. Results showed that higher concentrations of yeast led to prolonged normalization times. These findings demonstrate the potential of IoT-based sensors for accurately measuring water parameters and detecting microorganisms in water. The study highlights the importance of real-time monitoring and early detection of microbial contamination, enabling prompt actions to ensure water safety. In conclusion, this study emphasizes the significance of employing IoT-based sensors for efficient and reliable water quality monitoring.